(untitled) (International Journal of Engineering and Computer Science, 2018)
A database management system (DBMS) is a computer software application that interacts with the user, other applications, and the database itself to capture and analyze data. It allows organizations to conveniently develop databases for various applications by database administrators (DBAs) and other specialists. Information retrieval (IR) is the activity of obtaining information resources relevant to an information need from a collection of information resources. Searches can be based on or on full-text (or other contentbased) indexing. This was driven by the increasing functional requirements that modern full text search engines have to meet. Current database management systems (DBMS) are not capable of supporting such flexibility. However, with the increase of data to be indexed and retrieved and the increasing heavy workloads, modern search engines suffer from Scalability, reliability, distribution and performance problems. We present a new and simple way for integration and compare the performance of our system to the current implementations based on storing the full text index directly on the file system. Keywords: Full text search engines, DBMS IRS, DBMIRS, scalability.